Green fabrication of lanthanum doped zinc oxide nanoparticles (La-ZnONPs) via pineapple extract: Effects of calcination temperature on photocatalytic properties - Hussain, Rabia Tasaduq; Shazrin Afiqah, .; Jun Haslinda, Shariffuddin; Hamidah, Abdullah (IOP Publishing, 2025)
Disposal of pineapple waste is one of the main concern towards sustainability of an environment. In this work, the usage of pineapple waste in the synthesis of Zinc oxide nanoparticles (ZnONPs) could assist to reduce the waste and give us chance to utilize the waste in a useful manner. ZnONPs were produced via green approach employing the extract derived from pineapple waste peels, serving as reducing and stabilizing agent. This article demonstrates the effect of calcination temperatures on the La as a dopant for ZnONPs fabrication. Doping of the materials facilitated the nanoparticles to increase their stability by incorporation of some rare earth metals such as La. The materials (La-ZnONPs) with different calcination temperature were fabricated by co-precipitation method and thoroughly characterized by various spectroscopic techniques like Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Scanning Electron Microscopy – Energy Dispersive X-ray (SEM-EDX), and UV-Vis. Morphologically evidence given in SEM images that hexagonal shape converted into unique tiny flower images as the dopant added and calcination temperature increased wherein a gradual decrease from 27.83 to 23.02nm in crystallite size was noted with correspondence of rise at calcination temperature in doped La-ZnONPs. The lowest bandgap energy (3.11) with highest surface area along with the lowest crystallite size was obtained for La-ZnONPs calcined at a temperature of 600°C.